Análise de pastagens de capim-elefante submetidas aos sistemas de produção convencional e agroecológico com bovinos leiteiros - Charão, Pablo Santini (2006)
The use of elephantgrass (EG) under grazing is basically done at conventional strategy. Information and research about its use in agroecology production systems are scarce. Then, the objective of this work was to compare the elephantgrass pasture dynamic and performance submitted to the conventional and agroecology forage production systems. Evaluation of animal behavior also has done during the winter period in agroecology pasture. In conventional system the EG was established in singular form with 1.4m of space between lines. In agroecology system the space between lines was of 3m. At this system, the mixture of oat and ryegrass in the winter period and spontaneous growing species in the summer period had been. The nitrogenous fertilization was of 150kg/ha/year and had been with organic and synthetics fertilizers to the pastures of agroecology and conventional systems respectively. Holstein lactating cows receiving 3.5kg/day of concentrate in rotational grazing and varied stocking rate were used to evaluation. The forage mass, leaf lamina biomass (LLBEG) and structural composition of EG, pastures botanical composition and stocking rate were evaluated. Samples of grazing simulation were collected to do the quality analyses. The forage mass, LLBEG and stocking rate were bigger in the conventional pasture. Considering the mean data of experimentation, the results of stocking rate were similar and had been of 695 and 614kg/ha respectively to conventional and agroecology production. At this system the utilization of oat and ryegrass and the spontaneous growing species allowed the forage availability to be uniformed during the grazings. At animal behavior analysis the highest intensity of grazing was registered after each milking, observing a decrease lately during the day as well as during the night. Diurnal grazing time was longer than nocturnal. The oat + ryegrass grazing time is highest at period that elephantgrass show smallest leaf lamina percentage. The time of idle decrease and the rumination increase during the grazings because the leaf lamina percentage decrease and stems percentage increase of winter period species. The elephantgrass was grazed at all evaluations. The presence of different cycles species propitiated opportunity to the animals balance the roughage diet. The agroecology as much as conventional system showed high qualitative values considering the fertilization, manage and utilization time, in proposed strategy. The results show that the EG can be used under the agroecology systematic proposed.